Se m e n são raízes da equação x² - 5x + 6 = 0, então ( m/n + n/m) vale: *
Anexos:
![](https://pt-static.z-dn.net/files/d3c/3a633bf838b80c191cc2038cb23a2650.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
Resposta = 13/6
Explicação passo a passo:
Delta = -5^2 -4(1)(6)
Delta = 25 - 24
Delta = 1
m = 5+1 / 2
m = 3
n = 5-1 / 2
n = 2
m/n + n/m
3/2 + 2/3
9+4 / 6
13/6
ebermaluf:
ok. obriado
Perguntas interessantes
ENEM,
7 meses atrás
Matemática,
7 meses atrás
ENEM,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Física,
1 ano atrás
Inglês,
1 ano atrás